On the Dynamical Behaviors of a Cholera Model with Holling Type II Functional Response - Muhseen, Ahmed A; Zhou, Xueyong (Al-Nahrain Journal of Science, 2018)
In this paper a mathematical model that describes the flow of Cholera disease in a population is proposed and studied. It is assumed that the disease divided the population into five classes: susceptible individuals (S), asymptomatic infectious individuals , symptomatic infectious individuals removal individuals (R) and cholera population (B). The existence, uniqueness and boundedness of the solution of the model are discussed. The local and global stability of the model is studied. Finally the global dynamics of the proposed model is studied numerically.